2008
DOI: 10.1161/circresaha.108.178590
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Robust and Functional Vascular Networks In Vivo With Human Adult and Cord Blood–Derived Progenitor Cells

Abstract: Abstract-The success of therapeutic vascularization and tissue engineering will rely on our ability to create vascular networks using human cells that can be obtained readily, can be expanded safely ex vivo, and can produce robust vasculogenic activity in vivo. Here we describe the formation of functional microvascular beds in immunodeficient mice by coimplantation of human endothelial and mesenchymal progenitor cells isolated from blood and bone marrow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
490
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 446 publications
(530 citation statements)
references
References 41 publications
35
490
4
1
Order By: Relevance
“…Furthermore, it is suggested that 10T1/2 cells differentiate into SMCs or pericytes through heterotypic interactions with ECs (23,24,26). Recently, the perivascular/pericyte origin of bone marrow MSCs (32,33) has been identified, and the ability of these cells to differentiate to SMCs and stabilize nascent blood vessels (22,34,35) is being characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is suggested that 10T1/2 cells differentiate into SMCs or pericytes through heterotypic interactions with ECs (23,24,26). Recently, the perivascular/pericyte origin of bone marrow MSCs (32,33) has been identified, and the ability of these cells to differentiate to SMCs and stabilize nascent blood vessels (22,34,35) is being characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with mature endothelial cells that possess limited regenerative capacity 46 , ECFCs are endowed with high proliferative potential and robust vasculogenic properties that render these cells a promising opportunity for clinical use 47 . Our pre-clinical approach allowed ECFCs-MFSD2A to increase in situ EpDPE production, which in turn showed inhibitory effects on angiogenesis, vascular permeability and expression of inflammatory cytokines, thus leading to the clinical amelioration of intestinal inflammation ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have cocultured putative EPC with MSC or osteoblast-like cell types on the premise that this strategy will generate prevascular networks within bone tissue-engineered grafts to aid bone repair [13][14][15][16][17][18]. However, the majority of studies used ECs [19][20][21][22][23] rather than ECFC.…”
Section: Discussionmentioning
confidence: 99%